Aportes teóricos derivados de las investigaciones sobre el lenguaje entre el 2000 y el 2010 : una revisión (2012)
ABSTRACT: This article presents an analysis of content derived from a systematic review which picked up 57 studies that had the language as a central theme. The consulted investigations cast various theoretical contributions from which protrudes, firstly, the social origin of this process in both the filogenesis and the ontogenesis. In second place it can be affirmed that their development is affected negative or positively by variables such as nutrition, relationship with the parents, socialization at school and social atmosphere. Finally, the research about babies shows their active participation in the recognition of language, the act of pointing out as an important landmark in language development when provoking the combined attention, and finally the existent relationship between language and theory of mind.